The welfare impact of price changes on household welfare and inequality 1999-2010 - Jason Loughrey; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2011)
This paper provides a single welfare measure to show the effects of consumer price changes upon households in Ireland between 1999 and 2010. This measure combines an efficiency component using a Linear Expenditure System (LES) and an equity component using the Atkinson Social Welfare Function. The efficiency component includes the behavioural response to price changes for non-subsistence expenditures thereby producing a Cost of Living Index. The Atkinson Index of Inequality produces an inequality measure and this is combined with the Cost of Living Index to produce an overall welfare measure. This extends upon the existing Irish literature on this issue by accounting for this broader set of components. The results show that changes in the cost of living have differed substantially between households both in terms of demographics and the position of the household in the income distribution and that behavioural response can potentially improve the welfare position of households in response to price changes in most years.
urn:nbn:de:101:1-201106013305
Keywords: D12; D31; D63; E31; P46; 330; price; inflation; equivalent income; welfare; linear expenditure system; consumer price index; distribution; compensating variation; inequality aversion